2022
DOI: 10.1007/s00268-022-06806-4
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation and Obesity: Are There Any Differences in Outcomes?

Abstract: Introduction Kidney transplantation (KT) is the gold standard treatment for end‐stage renal disease (ESRD) patients. Obesity is a strong risk factor for developing cardiovascular disease, chronic kidney disease, and ESRD. This study aimed to investigate the outcomes of kidney transplantation in obese recipients. Material and methods We retrospectively reviewed the medical records of recipients from January 2016 to December 2021 in a single center. Outcomes in recipients of a kidney allograft with BMI ≥ 30 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…22 The authors observed higher rates of new onset diabetes and cardiovascular disease in the post-transplant BMI ≥25 kg/m 2 group and suggested that strategies to maintain a lower BMI in kidney transplant recipients may help prevent the associated impact of diabetes mellitus on graft and patient survival. However, another retrospective study of 467 kidney transplant recipients found no differences in the rate of acute rejection, delayed graft function, and survival rate between patients with BMI <30 kg/m 2 and those ≥30 kg/m 2 , 23 although this study did not distinguish between pre- and post-transplant BMI. Interestingly, one study exploring the effect of BMI <18.5 kg/m 2 on kidney transplantation found no impact on the rate of surgical complications or early postoperative kidney function but did find lower long-term graft survival in those with BMI <17 kg/m 2 .…”
Section: Kidney Transplantationcontrasting
confidence: 65%
“…22 The authors observed higher rates of new onset diabetes and cardiovascular disease in the post-transplant BMI ≥25 kg/m 2 group and suggested that strategies to maintain a lower BMI in kidney transplant recipients may help prevent the associated impact of diabetes mellitus on graft and patient survival. However, another retrospective study of 467 kidney transplant recipients found no differences in the rate of acute rejection, delayed graft function, and survival rate between patients with BMI <30 kg/m 2 and those ≥30 kg/m 2 , 23 although this study did not distinguish between pre- and post-transplant BMI. Interestingly, one study exploring the effect of BMI <18.5 kg/m 2 on kidney transplantation found no impact on the rate of surgical complications or early postoperative kidney function but did find lower long-term graft survival in those with BMI <17 kg/m 2 .…”
Section: Kidney Transplantationcontrasting
confidence: 65%
“…We read with interest the article by Mahmoudreza Moein et al recently published in WJS [1], in which the authors retrospectively analyzed a single‐center case series of 467 adult patients undergoing kidney transplantation (KT). The aim of this study was to demonstrate that BMI ≥ 30 is not an independent risk factor (RF) for KT outcome in terms of costs, 30‐day readmission, acute rejection (AR), delayed graft function (DGF), length of hospital stay, patient and graft survival.…”
mentioning
confidence: 99%
“…Based on this contemporary, single-center report, the answer to the question posed in the title is ''No'' [1].…”
mentioning
confidence: 99%